Transformasi Kurikulum Merdeka: Pengembangan Muatan Lokal untuk Meningkatkan Identitas Budaya - Ridwan Ali; Mulasi, Syibran (ISTIFHAM, 2023)
There are various efforts to increase awareness of local wisdom in Indonesia. This discussion aims to analyze the implementation of local content in schools to create awareness among students in preserving the nation's culture. This research uses a text analysis method relevant to the theme and objectives of the discussion, and data is taken using relevant references, regulations, and the reality that occurs in schools. The discussion results show that in the independent curriculum, educational units can add local content that the regional government has determined by local wisdom or regional characteristics. Provincial governments can allocate regional authority in developing local content curricula based on regional factors. This means that all cultural conditions and regional characteristics have sufficient space to be applied in the curriculum. Therefore, in determining local content options that will be implemented, local governments and schools still refer to applicable regulations and adapt them to the needs of local communities. From these findings, local governments and schools should synergize to maintain the nation's traditional and cultural values by implementing local wisdom in local content lessons in schools